Effects of Trauma-Related Shock on Myocardial Function in the Early Period Using Transthoracic Echocardiography - Dae Sung Ma (Journal of Trauma and Injury)
Purpose The present study aimed to analyze the effect of trauma-related shock on myocardial function in the early stages of trauma through transthoracic echocardiography (TTE) findings. Methods We performed a retrospective review and analysis of the medical records of patients aged ≥18 years who were evaluated by TTE within 2 days of admission for trauma-related shock (n=72). Patients were selected from a group of 739 patients admitted with trauma-related shock between January 2014 and December 2016. Results The incidence rate of myocardial dysfunction in the left ventricle (LV) was 6.8% (5/72), with rates of 7.7% (4/52) in the thoracic injury group and 5.0% (1/20) in the non-thoracic injury group. In the diastolic function of LV, relaxation abnormality was present in 55.8% (29/52) of patients in the thoracic injury group and 50% (10/20) of patients in the non-thoracic injury group. Conclusions This study may suggest that traumatic shock without thoracic injury may influence myocardial function in the early stages after trauma. Therefore, evaluation of myocardial function may be needed for patients experiencing shock after trauma, regardless of the presence of thoracic injury.